Neuropsychological Aspects of Children’s Somatic Disorders in Chronic Diseases: Diabetes and Short Stature in the Developmental Period - Maia Stanisławska-Kubiak; Katarzyna Wiecheć; Katarzyna Anna Majewska; Grażyna Teusz; Ewa Mojs; Andrzej Kędzia (Biomedicines, 2023)
Intellectual functioning studies carried out amongst children indicate that chronic diseases like type 1 diabetes and growth hormone deficiency (GHD), may, but do not necessarily, result in intellectual loss. Cognitive functions may decline as a child becomes older, as a disease persists over time and/or due to non-compliance with treatment recommendations or high stress levels. This study aimed to assess the cognitive functioning of children and youths with T1D and GHD-related short stature compared to healthy children. Methods: The study was carried out on 88 children with type 1 diabetes, 38 children suffering from short stature caused by (GHD), as well as a control group comprising 40 healthy children. Weschler’s tests were applied to measure intellectual and cognitive functions. Results: The results suggest that for children suffering from type 1 diabetes and short stature, their chronic childhood diseases per se do not impair cognitive development. It was observed that the higher the age of chronically ill children and the longer the disease persists, the lower their scores in individual cognitive subtests. For healthy children, age is correlated with the acquisition of particular skills and higher scores in specific subtests. Conclusions: On the basis of qualitative analysis of the cognitive functions subject to the study and close clinical observation of chronically ill children, we have been able to conclude that chronic diseases may alter cognitive functioning.